Low rents and low operating costs in social housing - an example from Germany - Marc Grossklos; André Müller (Acta Polytechnica CTU Proceedings, 2022)
The social housing project “PassiveHouseSocialPlus” in Germany with 42 residential apartments demonstrates how low rents and low operating costs can be combined. Different concepts for reducing operating costs were implemented and tested in one refurbished and one new apartment building. High energy efficiency for heating (passive house standard) and domestic hot water preparation were complemented by efficiency measures for household electricity (e.g. pre-installed energy-efficient kitchen appliances, LED lighting) and water savings through gray water usage for flushing toilets. Additionally, a flat rate billing scheme for most of the ancillary costs was established. Due to the overall low level of consumption, space heating and domestic hot water are also included in the flat rate with defined budgets. Displays in all apartments are informing the tenants about the used-up budget and show a forecast for the consumption of water and electricity until the end of the year. Results from more than two years of measuring are showing a low consumption of heat, which is about in the calculated range. The budgets for drinking water and electricity are slightly exceeded on average, nevertheless, the consumption levels are significantly below average consumption in Germany. The operating costs are around 30 % below the costs of comparable apartments in the same city.